2021
DOI: 10.4103/jmu.jmu_161_20
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus and Early Hemodynamic Changes in Fetus

Abstract: Background: Gestational diabetes mellitus (GDM) incidence can increase up to 14%. GDM creates a risk for developing type 2 diabetes mellitus after pregnancy. Umbilical artery (UA) and fetal middle cerebral artery (MCA) changes in GDM have been studied before. The previous studies have contradictory results. In the current study, we aim to detect and define the impairment of color Doppler ultrasound (CDUS) characteristics in UA and MCA for the pregnant with GDM. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…A prospective doppler study that was performed to predict GDM patients' perinatal outcomes showed that Middle Cerebral Artery Pulsatility Index could be an indicator; parallel to the current investigation, it found no important differences in umbilical artery values and reported that they cannot be used as an indicator [19]. A case-control study that evaluated early hemodynamic changes in the fetus aged 18-22 weeks old reported a decrease in the Middle Cerebral Artery peak systolic velocity values of the GDM group, and similar to our study, umbilical artery doppler parameters indicated no differences between the groups [20]. In addition to doppler measurements, maternal UtA doppler measurements are used to predict perinatal and maternal outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…A prospective doppler study that was performed to predict GDM patients' perinatal outcomes showed that Middle Cerebral Artery Pulsatility Index could be an indicator; parallel to the current investigation, it found no important differences in umbilical artery values and reported that they cannot be used as an indicator [19]. A case-control study that evaluated early hemodynamic changes in the fetus aged 18-22 weeks old reported a decrease in the Middle Cerebral Artery peak systolic velocity values of the GDM group, and similar to our study, umbilical artery doppler parameters indicated no differences between the groups [20]. In addition to doppler measurements, maternal UtA doppler measurements are used to predict perinatal and maternal outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…It is known that long-term uncontrolled hyperglycemia, chronic hypertension, preeclampsia, and IUGR can lead to placental vascular dysfunction with changes even in fetal circulation [ 53 , 82 , 104 , 105 , 106 ]. But the effect of metabolic changes due to diabetes mellitus during pregnancy on the fetus may be acidemia without hypoxemia, thus that redistribution seen in fetal hypoxemia may not occur even in severely compromised fetuses; and, therefore, it is of huge importance not to misrepresent this state by apparently normal fetal Doppler results [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The green squares represent each study individual SMD and the extending lines the 95% confidence intervals. The black diamond represents the overall estimate result [ 18 , 21 , 32 , 34 , 36 , 39 , 53 , 56 , 60 , 61 , 80 , 82 , 83 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that nutritional supplements such as inositol and α -lipoic acid, vitamin D, and metformin can reduce the risk of diabetes, while monitoring fetal hemodynamic parameters can reduce the risk of hypertension and preeclampsia [ 7 , 8 ]. Therefore, the use of color Doppler ultrasound to monitor the hemodynamic parameters of fetal MCA in late pregnancy can be used to predict fetal hypoxia and severity [ 9 ]. When the fetus is in intrauterine hypoxia, the blood flow RI increases after RA contraction, and the blood flow redistribution is realized.…”
Section: Introductionmentioning
confidence: 99%